2019
DOI: 10.1186/s41072-019-0046-5
|View full text |Cite
|
Sign up to set email alerts
|

The ostensible tension between competition and cooperation in ports: a case study on intra-port competition and inter-organizational relations in the Rotterdam container handling sector

Abstract: Strategic alliances in the container shipping sector, and requirements imposed by consolidated hinterland modalities such as trains and barges, have resulted in container terminals facing increasing pressures to cooperate to handle increasingly intertwined container flows. However, concession agreements and market conditions often also pressure terminals to compete. This paper aims to help understand how pressures for competition and cooperation conflict, what problems this causes, what drives these tensions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Case study analysis is the second most frequently employed methodological approach found in COB research, comprising 19% of our sample. Castelein et al (2019) conduct a case study of the Port of Rotterdam to identify the underlying problems caused by interorganizational cooperation and competition under pressure. Their case study reveals the significance of mutual trust, value sharing, and unity among intermodal transportation parties, to maintain a healthy balance between cooperation and competition.…”
Section: Methodological Approaches Employed In Cob Researchmentioning
confidence: 99%
“…Case study analysis is the second most frequently employed methodological approach found in COB research, comprising 19% of our sample. Castelein et al (2019) conduct a case study of the Port of Rotterdam to identify the underlying problems caused by interorganizational cooperation and competition under pressure. Their case study reveals the significance of mutual trust, value sharing, and unity among intermodal transportation parties, to maintain a healthy balance between cooperation and competition.…”
Section: Methodological Approaches Employed In Cob Researchmentioning
confidence: 99%
“…On the other hand, competition as well as cooperation among major participants in the shipping supply chains not only are important spur and propellant to promote performance of the shipping industry, but also both need to be maintained within a reasonable range. Between ports and shipping enterprises, there is already fierce competition in infrastructure, price, service and other “soft” aspects, too (Castelein et al, 2019), and facing the wave of globalization and digital shipping, vertical and horizontal forms of cooperation have gradually emerged (Alvarez‐SanJaime et al, 2013), to fetch the effect of “1 + 1 > 2”. For example, in 1996, China formally proposed to build “combined ports” centered on Shanghai and radiating Jiangsu and Zhejiang ports.…”
Section: Introductionmentioning
confidence: 99%
“…Between ports and shipping enterprises, there is already fierce competition in infrastructure, price, service and other "soft" aspects, too (Castelein et al, 2019), and facing the wave of globalization and digital shipping, vertical and horizontal forms of cooperation have gradually emerged (Alvarez-SanJaime et al, 2013), to fetch the effect of "1 + 1 > 2". For example, in 1996, China formally proposed to build shan Port has ranked first in the world for 13 consecutive years.…”
mentioning
confidence: 99%
“…Development of fuel efficiency, improvement of energy efficiency, change of transportation architecture, development and smartening of ports, development of Network data envelopment analysis appropriate infrastructure in ports, utilization of modern technologies in ports, adoption of ICT, intelligent port systems, port efficiency, port operator, port tariffs, trade flows, trade imbalances, trade volume, trade complementarity, maritime industry structure, supply line services, position regulations in the global transit network, distance centralization, the ship operating costs, trade facilitation, freight, transit volume and value, type of production, international maritime agents and transit costs must be considered to save energy and achieve an efficient allocation of available resources (Castelein et al, 2019).…”
Section: Introductionmentioning
confidence: 99%